Ten Common Flowering Trees of the Tampa Bay Area: ENH1244/EP505, 4/2015 - Hasing, Gitta; Koeser, Andrew K.; Knox, Gary W.; Friedman, Melissa H. (EDIS, 2016)
Blooming trees serve as key focal points in the urban landscape. Florida’s flowering trees can be quite spectacular and leave you wondering, Wow, what tree is that? This 7-page guide will assist you in identifying the 10 most common flowering trees that grow in the Tampa Bay area of Florida. It is an efficient resource for master gardeners, novice tree inventory crews, 4-H forestry teams, and others interested in basic flowering tree identification. Written by Gitta Hasing, Andrew K. Koeser, Gary W. Knox, and Melissa H. Friedman, and published by the Environmental Horticulture Department, April 2015. ENH1244/EP505: Ten Common Flowering Trees of the Tampa Bay Area (ufl.edu)